Unmasking the nature of granulomatosis with polyangiitis – a diagnostic odyssey revealed through a compelling case report - Sajdak, Piotr; Krużel, Aleksandra; Stodolak, Marcel; Bednarski, Artur; Ziajor, Seweryn; Turski, Mikołaj; Żurowska, Klaudia; Kłos, Kamil; Tomasik, Justyna; Dębik, Marika; Szydłowski, Łukasz (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Granulomatosis with polyangiitis (GPA), formerly known as Wegener’s granulomatosis, presents a formidable challenge in the realm of autoimmune diseases. Granulomatosis, characterized by vasculitis and granuloma formation, exhibits diverse clinical manifestations. The rarity of GPA is evident, with an estimated incidence between 0.4 and 11.9 cases per 1 million person-years. The aim of this report is to show the complex diagnostic challenges inherent in GPA, demonstrating the diagnostic process from initial symptoms. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. This case report unfolds the diagnostic journey of a 52-year-old Caucasian male. The presented case, initially suspected as a respiratory infection, led to a comprehensive investigation owing to persistent symptoms, abnormal blood counts, and elevated inflammatory markers. This narrative aims to depict the patient’s diagnostic journey. Key diagnostic tools include ANCA testing, imaging studies, and tissue biopsy. Pulmonary nodules, lymphangitic changes, and renal involvement culminating in a GPA diagnosis confirmed by positive ANCA and anti-PR3 antibodies. The successful management of this case involved a tailored therapeutic regimen, including cyclophosphamide and methylprednisolone, addressing both vasculitic and renal components. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. This case contributes to the understanding of atypical presentations of GPA, emphasizing the importance of a holistic and dynamic diagnostic approach.